1999
DOI: 10.1094/mpmi.1999.12.11.1000
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhiza-Induced Changes in Disease Severity and PR Protein Expression in Tobacco Leaves

Abstract: The development of leaf disease symptoms and the accumulation of pathogenesis-related (PR) proteins were monitored in leaves of tobacco (Nicotiana tabacum cv. Xanthinc) plants colonized by the arbuscular mycorrhizal fungus Glomus intraradices. Leaves of mycorrhizal plants infected with the leaf pathogens Botrytis cinerea or tobacco mosaic virus showed a higher incidence and severity of necrotic lesions than those of nonmycorrhizal controls. Similar plant responses were obtained at both low (0.1 mM) and high (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(79 citation statements)
references
References 43 publications
4
73
2
Order By: Relevance
“…Our data are in agreement with previous studies, indicating an increase in symptom development and virus accumulation in leaves of virus-infected mycorrhizal plants (Daft and Okusanya 1973;Shaul et al 1999). AM fungi are known to increase the uptake of nutrients, especially phosphorous and nitrogen into their host plants (Guether et al 2009;Javot et al 2007).…”
Section: Effect Of Mycorrhiza On Viral Infectionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data are in agreement with previous studies, indicating an increase in symptom development and virus accumulation in leaves of virus-infected mycorrhizal plants (Daft and Okusanya 1973;Shaul et al 1999). AM fungi are known to increase the uptake of nutrients, especially phosphorous and nitrogen into their host plants (Guether et al 2009;Javot et al 2007).…”
Section: Effect Of Mycorrhiza On Viral Infectionsupporting
confidence: 93%
“…3). This is in agreement with a lower accumulation and a delay in activation of PR1 and PR3 proteins observed in mycorrhizal tobacco (Shaul et al 1999) and associated with enhanced virus infectivity.…”
Section: Effect Of Mycorrhiza On Viral Infectionsupporting
confidence: 89%
“…Increased multiplication of plant viruses by mycorrhizal colonization of the host plants was revealed previously [17]. Yet, only one report [18] showed the enhanced disease severity compared with non-mycorrhizal controls. Based on investigations involving three viruses (Tomato acuba mosaic virus, Potato virus X, Arabis mosaic virus) in three different hosts (tomato, petunia, strawberry), Daft and Okusanya [17] revealed that the amount of extractable virus particles is higher for mycorrhizal than non-mycorrhizal plants.…”
Section: Discussionmentioning
confidence: 79%
“…Nonetheless, for both foliar endophytic fungi (FEE) and arbuscular mycorrhizal fungi (AMF) there is accumulating evidence that these fungi provide previously under-appreciated beneficial effects for their hosts. Specifically, recent work has demonstrated that, under some circumstances, both types of endophytes (FEE in leaves and AMF in roots) can enhance host resistance against attack and damage by pathogens (Smith 1988, Smith and Gianinazzi-Pearson 1988, Newsham et al 1995, Shaul et al 1999, Borowitz 2001, Evans et al 2003, Garmendia 2004, Holmes et al 2004, Herre et al 2005a, b, Rubini et al 2005, Van Bael et al 2005; but see Faeth 2002). Discovering what these effects are, clarifying their proximal mechanisms, and understanding the ultimate selective pressures that influence them are primary goals for the study of the evolutionary ecology of endophytehost interactions (Carroll 1991, Herre et al 1999).…”
Section: Introductionmentioning
confidence: 99%